Factors influencing the efficacy of two organophosphate insecticides in controlling California red scale, Aonidiella aurantii (Maskell). A basis for reducing spray application volume in Mediterranean conditions - Garcerá, Cruz; Moltó, Enrique; Chueca, Patricia (2017)
Background: Because society is seeking ways to lessen the environmental impact of agricultural activity, dose adjustment has become a key issue in current plant protection treatments with high spray application volumes, such as on citrus plants. This work investigates, in field conditions, the factors affecting the efficacy of organophosphate insecticides against California red scale (CRS), Aonidiella aurantii (Maskell), when the delivery rate is decreased. Insecticide rate changes were induced by modifying the spray application volumes of two commercial organophosphate pesticides based on chlorpyrifos and chlorpyrifos-methyl. Results: Results showed that, with increase in the spray volume, the coverage and the uniformity of deposition on the canopy increased, but final infestation depended neither on the spray application volume nor on the coverage. Furthermore, final infestation significantly depended on the pest pressure in the plot and the spray volume applied per unit volume of canopy (L m(-3) canopy). Moreover, it was found that the final infestation was influenced by the efficiency of deposition in the applications that were carried out against the second-generation of CRS. Conclusion: Because the spray application volume did not affect the final infestation, this research introduces the possibility that reducing the doses of current citrus organophosphate treatments may still allow effective plant protection in Mediterranean conditions.